The economics of greenhouse gas mitigation in developing Asia - Lara Aleluia Reis; Johannes Emmerling; Massimo Tavoni; David Raitzer (Asian Development Bank (ADB), 2016)
Developing Asia has the world's fastest greenhouse gas emissions growth. This study uses an economy-energy-climate model to assess the effects of Paris Agreement pledges on Asia, in comparison with business as usual (BAU) and more ambitious scenarios. Results confirm that pledges must be strongly increased in ambition to achieve the Paris Agreement's goal of less than 2 degrees Celsius (2êC) warming. The policy costs of Asia's pledges are found to be less than 1% of gross domestic product (GDP) through 2050, while 2êC scenarios may cost less than 2% of GDP. However, costs are sensitive to assumptions about international carbon markets and mitigation timing, with costs for 2êC scenarios doubling in the absence of carbon trade, and increasing the later that mitigation is initiated. Under the 2êC scenarios, annual average energy supply investments are about 300 billion above the BAU levels through 2050. Mitigation policy may substantially reduce air pollution mortality, with up to 600,000 fewer deaths in Asia annually by 2050. When costs, benefits of avoided climate change, and cobenefits are considered together, investment in mitigation policy is found to have substantial economic returns for the region - if action is taken rapidly and international carbon market mechanisms are implemented.
Keywords: C61; D58; Q52; Q53; Q54; 330; climate change; energy; greenhouse gas; mitigation; Paris Agreement